Homoeopathic Management of Arthritis – A Retrospective Study (Advancements in Homeopathic Research, 2023)
Introduction: Arthritis is a term used for tenderness  in the joints with swelling. It can affect one or more  joints and is a gradually progressive disease which  is not usually noticed in the early stages. WHO in  its recent report states that musculoskeletal disorders  are one of the disability causing disorders in the  recent era which needs immediate and emergency  care. Osteoarthritis (OA) and Rheumatoid arthritis  (RA) are the common forms of arthritis presented  in most of the peoples, and Fibromyalgia (FM)  is a condition known as chronic pain syndrome  affects 2% of population. Homoeopathy is a system  which is can remove the sufferings permanently  when administered constitutionally by exact similar  remedy, potency and dose with frequent repetitions.Materials and Methods: A retrospective analysis  had been done with 535 patients who had visited  general OPD 2 at NHRIMH, Kottayam with  rheumatological symptoms for about 1 year duration  (between January 2022 to December 2022) to find  out the frequently indicated medicines.  Results: In this retrospective study among 535patients  it had been observed that 32% (172) patients were  between 51 and 60 age as maximum and 1% (2)  patients were between 81-90 as minimum. Females  were more affected than males. 57 (11%) old patients  and 478 (89%) new patients had been noted during  this study period. 22% (116) patients and had been  diagnosed with Osteoarthritis (OA) as maximum  and 4% (21) patients with fibromyalgia as minimum  Sulphur 17%(87) and Rhustox 15% (78) had been  prescribed in maximum patients and Iris versicularis  in less patients2% (12).  Conclusion: This retrospective study proves that all  the rheumatologic diseases when treated with basic  principles of homoeopathy and individualization, it  is possible to make a permanent cure without side  effects.
Keywords: Arthritis; Osteoarthritis (OA); Rheumatoid arthritis (RA); Fibromyalgia (FM); Homoeopathy; Individualization